2022
DOI: 10.1099/jmm.0.001579
|View full text |Cite
|
Sign up to set email alerts
|

Shiga toxin-producing Escherichia coli clonal complex 32, including serotype O145:H28, in the UK and Ireland

Abstract: Introduction. Shiga toxin-producing Escherichia coli (STEC) O157:H7 has been the most clinically significant STEC serotype in the UK for over four decades. Over the last 10 years we have observed a decrease in STEC O157:H7 and an increase in non-O157 STEC serotypes, such as O145:H28. Gap Statement. Little is known about the microbiology and epidemiology of STEC belonging to CC32 (including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 47 publications
3
8
0
Order By: Relevance
“…2). As observed with other non-O157 STEC CCs in England [17][18][19], London (CC25 n=103/315, 33 %, CC33 n=189/528, 36 %, CC442 n=184/574, 32 %) and the South East of England (CC442 n=200/574, 35 %; CC33 n=180/528, 34 %, CC25 n=118/315, 37 %) were the two regions reporting the highest numbers of cases of LEE-negative STEC (Fig. 3).…”
Section: Clonal Complex Microbiology and Typing Datasupporting
confidence: 81%
See 1 more Smart Citation
“…2). As observed with other non-O157 STEC CCs in England [17][18][19], London (CC25 n=103/315, 33 %, CC33 n=189/528, 36 %, CC442 n=184/574, 32 %) and the South East of England (CC442 n=200/574, 35 %; CC33 n=180/528, 34 %, CC25 n=118/315, 37 %) were the two regions reporting the highest numbers of cases of LEE-negative STEC (Fig. 3).…”
Section: Clonal Complex Microbiology and Typing Datasupporting
confidence: 81%
“…In common with other non-O157 STEC clonal complexes in England [17][18][19], notifications of STEC belonging to CC25, CC33 and CC442 have increased every year since 2014, most likely due to the increasing number of frontline diagnostic laboratories implementing commercial PCR assays that target stx [2]. However, it is possible that this change in the diagnostic algorithm is masking a true increase in non-O157 STEC in England.…”
Section: Discussionmentioning
confidence: 99%
“…As observed with other STEC serotypes, specifically STEC O157:H7, STEC O26:H11 and STEC O145:H28 [44][45][46], most cases of E. coli encoding stx2f were female, a high proportion of cases were children under the age of 5 years old, and notifications peaked in later summer, early autumn. Prager et al [24] [24] reported a higher proportion of cases in children in Germany, and Friesema et al…”
Section: Discussionsupporting
confidence: 69%
“…However, we cannot rule out a true increase in the burden of infectious disease caused by E. coli encoding stx2f. Unlike other non-O157 STEC serotypes that we have reviewed recently where most cases were identified in the South of England, the same region where the highest density of laboratories using PCR were located [42][43][44][45], most cases of E. coli encoding stx2f were located in the North of England. As STEC surveillance is not consist across the country, it is difficult to interpret the meaningfulness of this geographical clustering, but it may be indicative of a local animal or environmental source.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation